EKSPLORASI ETNOMATEMATIKA PADA MASJID AGUNG KOTA TASIKMALAYA - Widya Saviraningrum; Wahidin Wahidin (LPPM Universitas Bina Bangsa, 2023)
Cultural mathematics is a way of designing mathematics that is meaningful and relatable to cultural communities. Cultural learning is more interesting and fun to learn because of the socio-cultural construction in which mathematics has been embedded in human history and activities. Learning that is oriented towards mathematics and culture is called ethnomathematics. Each area has historical buildings that can be observed by culture. One of the historical places in Tasikmalaya, West Java, is the Great Mosque of Tasikmalaya City. The purpose of this study was to explore the mathematical concepts contained in the Great Mosque of Tasikmalaya City and to find out the development of numeration in the Great Mosque of Tasikmalaya City. This type of research is qualitative research with an ethnographic approach. Data collection was carried out using observation, interviews, case studies, and documentation. The results of this study are the mathematical concepts contained in the Great Mosque of Tasikmalaya City, namely the concept of flat shape, geometric concept, arithmetic sequence concept, palindrome number concept, geometric reflection transformation concept, and numeration development